Long-life OPzV storage battery and application thereof
By using Patton powder and reddish in OPzV batteries, combined with extrusion paste and high-temperature curing technology, the problem of short life of OPzV batteries is solved, and the long life and consistency of the battery is significantly improved.
Patent Information
- Application Number
- CN202411881518.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-11
AI Technical Summary
The lifespan of existing OPzV batteries is relatively short. The conversion of the positive electrode plate α-PbO2 to β-PbO2 leads to a decrease in mechanical strength and the failure of active substances, resulting in the end of battery life.
Patton powder is used as the active substance of the positive electrode plate, red elixir is added, and made by extrusion paste and high-temperature curing processes. The negative electrode plate is coated on the negative electrode grid with negative electrode lead paste and then cured.
By increasing the binding force between lead paste and lead core, the softening and shedding time of lead paste is extended, the long life of lead acid batteries is significantly improved, and the consistency and reliability of the battery pack are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of storage batteries, and in particular to a long-life OPzV storage battery and application thereof. Background Art
[0002] As a DC power source for energy storage, OPzV batteries are widely used for peak and frequency regulation on the user energy storage side, power generation side, and grid side. OPzV batteries have a long cycle life and can be used for deep cycle discharge. They can be connected in series or in parallel according to actual needs. The main life attenuation and failure modes are deformation of the positive plate, mudding and shedding of the lead paste, and irreversible sulfation. The essence is the change of the lead paste crystals. The bonding force between the lead dioxide crystals deteriorates, resulting in extreme softening and failure of the lead paste. Therefore, the key to improving the cycle life of lead-acid batteries is to design a battery with high durability and good plate consistency, so that the lead paste crystals change slowly during use and the softening and shedding time of the lead paste is extended.
[0003] Under the background of increasingly higher requirements for the service life of OPzV batteries, the OPzV batteries produced by traditional Shimadzu powder low-temperature curing process have an average life of 8-10 years, which is shorter than that of lithium batteries.
[0004] The active material of the positive plate of a lead-acid battery is composed of α-PbO2 and β-PbO2. The structure of α-PbO2 is relatively coarse, with high mechanical strength and is easy to connect. It can form a relatively coarse and strong skeleton and mesh structure, increase the mechanical strength of the plate, facilitate current conduction, stabilize the active material, etc. β-PbO2 is attached to the skeleton formed by α-PbO2, and its charge capacity is much stronger than that of α-PbO2. Lead oxide forms lead sulfate after discharge, and is reduced to lead oxide during charging. However, in a lead-acid environment, lead sulfate can only form β-PbO2. When the battery is discharged deeply, α-PbO2 will participate in the discharge and be converted into β-PbO2. Therefore, during the charge and discharge cycle of the lead-acid battery, the α-PbO2 on the positive plate will slowly be converted into β-PbO2 with low mechanical strength, the conductive mesh structure will be weakened, the active material will fail, soften, or even fall off, and the life of the lead-acid battery will end.
[0005] Barton powder is mainly orthorhombic crystal type, the lead powder particles are spherical, and the particle size is larger than that of Shimadzu powder. It is easier to form 4BS through high-temperature curing, and form good adhesion between the lead paste and the grid. After chemical formation, it is converted into α-PbO2, forming a relatively coarse and solid skeleton and network structure, thereby extending the life of the battery.
[0006] Lead-acid batteries have the advantages of safety, reliability, lower cost, and higher battery recycling value. With the continuous development of the OPzV battery market, solutions need to be proposed to address the problems of short life and poor consistency of lead-acid OPzV batteries. Summary of the invention
[0007] In view of the defects of the prior art, the object of the present invention is to provide a long-life OPzV battery and its application to solve the problems raised in the above background technology.
[0008] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a long-life OPzV storage battery, which is composed of a plate, a separator, a gel electrolyte, a shell, and a conductive lead part; The electrode plate is composed of a positive electrode plate and a negative electrode plate. The positive electrode plate is produced by Barton, red lead is added, and it is made by extrusion and high-temperature curing process. The negative electrode plate is made by coating negative lead paste on the negative electrode grid and then curing it.
[0009] Preferably, the preparation method of Patton powder is as follows: a lead ingot is heated to a molten state in a lead melting pot, and then a 450°C lead liquid is introduced into a gas phase oxidation chamber, and fresh air is introduced at the same time. The molten lead liquid is stirred into fine droplets by a high-speed rotating impeller in the gas phase oxidation chamber, so that the lead liquid is fully in contact with the air, and is oxidized to form lead oxide particles, and the lead powder particles that meet the particles are blown to a cyclone settler by negative pressure wind for cooling and sedimentation, and are collected by a pulse bag; the temperature of the gas phase oxidation chamber is 450°C, the oxidation degree of the lead powder is 78-82%, and the apparent specific gravity is 1.70-1.80 g / cm 3 . .
[0010] Preferably, the lead powder has an oxidation degree of 78-82% and an apparent specific gravity of 1.70-1.80 g / cm 3 , average diameter 4μm, specific surface area 1.2~1.4m 2 / g, the particles are spherical.
[0011] Preferably, the weight ratio of barton powder to red lead is 3:1.
[0012] Preferably, the lead paste raw materials in the positive plate paste extrusion process are prepared according to the following weight: 4-4.5 parts of sulfuric acid, 18-19 parts of water, 18.5-19.5 parts of red lead, and 57-59 parts of Patton powder.
[0013] Preferably, the curing temperature of the positive electrode curing process is 65-80°C, the humidity is 98%, the high temperature time is not less than 12h, and the curing process temperature is not less than 65°C.
[0014] Preferably, the negative electrode lead paste is prepared from the following raw materials by weight: 0.1-0.2 parts of lignin, 0.2-0.3 parts of acetylene black, 0.4-0.6 parts of barium sulfate, 3-4 parts of sulfuric acid, 12-14 parts of water, and 81-84.4 parts of lead powder.
[0015] Preferably, the positive plate ribs in the positive plate and the negative plate are lead-calcium-tin-aluminum alloy, and the negative plate grids are lead-calcium-tin-aluminum alloy.
[0016] The invention also provides an application of a long-life OPzV storage battery in a lead-acid storage battery.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The invention is characterized in that the positive electrode plate uses Barton powder, red lead is added, and a paste extrusion process and a high-temperature curing process are adopted. The Barton powder particles are spherical and have an average diameter of about 4 μm. The high-temperature curing improves the bonding force between the lead paste and the lead core, thereby significantly improving the long life of the lead-acid battery, and also improving the consistency and reliability of the battery pack. DETAILED DESCRIPTION
[0018] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] A long-life OPzV storage battery of this embodiment is composed of a plate, a separator, a gel electrolyte, a shell, and a conductive lead part; The electrode plate is composed of a positive electrode plate and a negative electrode plate. The positive electrode plate is produced by Barton, red lead is added, and it is made by extrusion and high-temperature curing process. The negative electrode plate is made by coating negative lead paste on the negative electrode grid and then curing it.
[0020] The preparation method of the Baton powder of this embodiment is as follows: a lead ingot is heated to a molten state in a lead melting pot, and then a lead liquid at 450°C is introduced into a gas phase oxidation chamber, and fresh air is introduced at the same time. In the gas phase oxidation chamber, a high-speed rotating impeller stirs the molten lead liquid into fine droplets, so that the lead liquid is fully in contact with the air and is oxidized to form lead oxide particles. The lead powder particles that meet the particles are blown to a cyclone settler by negative pressure wind for cooling and sedimentation, and are collected by a pulse bag.
[0021] The lead powder in this embodiment has an oxidation degree of 78-82% and an apparent specific gravity of 1.70-1.80 g / cm 3 , average diameter 4μm, specific surface area 1.2~1.4m 2 / g, the particles are spherical.
[0022] The weight ratio of barton powder to red lead in this embodiment is 3:1.
[0023] The lead paste raw materials in the positive plate paste extrusion process of this embodiment are prepared according to the following weight: 4-4.5 parts of sulfuric acid, 18-19 parts of water, 18.5-19.5 parts of red lead, and 57-59 parts of Patton powder.
[0024] The positive electrode curing process of this embodiment has a curing temperature of 65-80° C., a humidity of 98%, a high temperature time of not less than 12 hours, and a curing process temperature of not less than 65° C.
[0025] The negative electrode lead paste of this embodiment is prepared from the following raw materials by weight: 0.1-0.2 parts of lignin, 0.2-0.3 parts of acetylene black, 0.4-0.6 parts of barium sulfate, 3-4 parts of sulfuric acid, 12-14 parts of water, and 81-84.4 parts of lead powder.
[0026] In the positive plate and the negative plate of this embodiment, the positive plate ribs are made of lead-calcium-tin-aluminum alloy, and the negative plate grids are made of lead-calcium-tin-aluminum alloy.
[0027] The present embodiment is an application of a long-life OPzV battery in a lead-acid battery.
[0028] Example 1 A long-life OPzV storage battery of this embodiment is composed of a plate, a separator, a gel electrolyte, a shell, and a conductive lead part; The electrode plate is composed of a positive electrode plate and a negative electrode plate. The positive electrode plate is produced by Barton, red lead is added, and it is made by extrusion and high-temperature curing process. The negative electrode plate is made by coating negative lead paste on the negative electrode grid and then curing it.
[0029] The preparation method of the Baton powder of this embodiment is as follows: a lead ingot is heated to a molten state in a lead melting pot, and then a lead liquid at 450°C is introduced into a gas phase oxidation chamber, and fresh air is introduced at the same time. In the gas phase oxidation chamber, a high-speed rotating impeller stirs the molten lead liquid into fine droplets, so that the lead liquid is fully in contact with the air and is oxidized to form lead oxide particles. The lead powder particles that meet the particles are blown to a cyclone settler by negative pressure wind for cooling and sedimentation, and are collected by a pulse bag.
[0030] The lead powder in this embodiment has an oxidation degree of 8% and an apparent specific gravity of 1.75 g / cm 3 , average diameter 4μm, specific surface area 1.3m 2 / g, the particles are spherical.
[0031] The weight ratio of barton powder to red lead in this embodiment is 3:1.
[0032] The lead paste raw materials in the positive plate paste extrusion process of this embodiment are prepared according to the following weight: 4-4.5 parts of sulfuric acid, 18.5 parts of water, 19 parts of red lead, and 58 parts of Patton powder.
[0033] The positive electrode curing process of this embodiment has a curing temperature of 70° C., a humidity of 98%, a high temperature time of not less than 12 hours, and a curing process temperature of not less than 65° C.
[0034] The negative electrode lead paste of this embodiment is prepared from the following raw materials by weight: 0.15 parts of lignin, 0.25 parts of acetylene black, 0.5 parts of barium sulfate, 3.5 parts of sulfuric acid, 13 parts of water, and 82 parts of lead powder.
[0035] In the positive plate and the negative plate of this embodiment, the positive plate ribs are made of lead-calcium-tin-aluminum alloy, and the negative plate grids are made of lead-calcium-tin-aluminum alloy.
[0036] The present embodiment is an application of a long-life OPzV battery in a lead-acid battery.
[0037] Example 2 A long-life OPzV storage battery of this embodiment is composed of a plate, a separator, a gel electrolyte, a shell, and a conductive lead part; The electrode plate is composed of a positive electrode plate and a negative electrode plate. The positive electrode plate is produced by Barton, red lead is added, and it is made by extrusion and high-temperature curing process. The negative electrode plate is made by coating negative lead paste on the negative electrode grid and then curing it.
[0038] The preparation method of the Baton powder of this embodiment is as follows: a lead ingot is heated to a molten state in a lead melting pot, and then a lead liquid at 450°C is introduced into a gas phase oxidation chamber, and fresh air is introduced at the same time. In the gas phase oxidation chamber, a high-speed rotating impeller stirs the molten lead liquid into fine droplets, so that the lead liquid is fully in contact with the air and is oxidized to form lead oxide particles. The lead powder particles that meet the particles are blown to a cyclone settler by negative pressure wind for cooling and sedimentation, and are collected by a pulse bag.
[0039] The lead powder in this embodiment has an oxidation degree of 78% and an apparent specific gravity of 1.70 g / cm 3 , average diameter 4μm, specific surface area 1.2m 2 / g, the particles are spherical.
[0040] The weight ratio of barton powder to red lead in this embodiment is 3:1.
[0041] The lead paste raw materials in the positive plate paste extrusion process of this embodiment are prepared according to the following weight: 4 parts of sulfuric acid, 18 parts of water, 18.5 parts of red lead, and 57 parts of Patton powder.
[0042] The positive electrode curing process of this embodiment has a curing temperature of 65° C., a humidity of 98%, a high temperature time of not less than 12 hours, and a curing process temperature of not less than 65° C.
[0043] The negative electrode lead paste of this embodiment is prepared from the following raw materials by weight: 0.1 parts of lignin, 0.2 parts of acetylene black, 0.4 parts of barium sulfate, 3 parts of sulfuric acid, 12 parts of water, and 81 parts of lead powder.
[0044] In the positive plate and the negative plate of this embodiment, the positive plate ribs are made of lead-calcium-tin-aluminum alloy, and the negative plate grids are made of lead-calcium-tin-aluminum alloy.
[0045] The present embodiment is an application of a long-life OPzV battery in a lead-acid battery.
[0046] Example 3 A long-life OPzV storage battery of this embodiment is composed of a plate, a separator, a gel electrolyte, a shell, and a conductive lead part; The electrode plate is composed of a positive electrode plate and a negative electrode plate. The positive electrode plate is produced by Barton, red lead is added, and it is made by extrusion and high-temperature curing process. The negative electrode plate is made by coating negative lead paste on the negative electrode grid and then curing it.
[0047] The preparation method of the Baton powder of this embodiment is as follows: a lead ingot is heated to a molten state in a lead melting pot, and then a lead liquid at 450°C is introduced into a gas phase oxidation chamber, and fresh air is introduced at the same time. In the gas phase oxidation chamber, a high-speed rotating impeller stirs the molten lead liquid into fine droplets, so that the lead liquid is fully in contact with the air and is oxidized to form lead oxide particles. The lead powder particles that meet the particles are blown to a cyclone settler by negative pressure wind for cooling and sedimentation, and are collected by a pulse bag.
[0048] The lead powder in this embodiment has an oxidation degree of 82% and an apparent specific gravity of 1.80 g / cm 3 , average diameter 4μm, specific surface area 1.4m 2 / g, the particles are spherical.
[0049] The weight ratio of barton powder to red lead in this embodiment is 3:1.
[0050] The lead paste raw materials in the positive plate paste extrusion process of this embodiment are prepared according to the following weight: 4.5 parts of sulfuric acid, 19 parts of water, 19.5 parts of red lead, and 59 parts of Patton powder.
[0051] The positive electrode curing process of this embodiment has a curing temperature of 80° C., a humidity of 98%, a high temperature time of not less than 12 hours, and a curing process temperature of not less than 65° C.
[0052] The negative electrode lead paste of this embodiment is prepared from the following raw materials by weight: 0.2 parts of lignin, 0.3 parts of acetylene black, 0.6 parts of barium sulfate, 4 parts of sulfuric acid, 14 parts of water, and 84.4 parts of lead powder.
[0053] In the positive plate and the negative plate of this embodiment, the positive plate ribs are made of lead-calcium-tin-aluminum alloy, and the negative plate grids are made of lead-calcium-tin-aluminum alloy.
[0054] The present embodiment is an application of a long-life OPzV battery in a lead-acid battery.
[0055] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not use Patton powder, but uses Shimadzu powder, which has the same proportion as the paste, uses a high temperature curing process, and has the same negative plate. The apparent specific gravity of Shimadzu powder is 1.40-1.50 g / cm3, and the degree of oxidation is 72-78%.
[0056] Comparative Example 2 The difference between Comparative Example 1 and Example 1 is that Comparative Example 2 uses Barton powder and adopts a low-temperature curing process. The first curing stage is 45°C and the humidity is 90%. After 48 hours, it is dried at 70°C until the moisture content of the plate is less than 1%.
[0057] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses Shimadzu powder with an apparent specific gravity of 1.40-1.50 g / cm3, an oxidation degree of 72-78%, and an unchanged paste ratio. It is produced by a positive plate extrusion paste process and is cured by a low-temperature curing process. The first curing stage is 45°C and a humidity of 90%. After 48 hours, it is dried at 70°C until the moisture content of the plate is less than 1%.
[0058] Sample batteries were assembled for the above Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively, and subjected to 5C, 100% DOD cycle test. The test was terminated when the 10h rate was lower than 80%.
[0059] Table 1:
[0060] As shown in Table 1, the OPzV battery prepared by the present invention uses Patton powder for the positive plate, adds red lead, adopts the paste extrusion process, and is produced by the high-temperature curing process. The grid alloy uses a high-tin lead-calcium alloy, and the negative plate is a coated negative plate, which is assembled with a PE plus AGM composite separator. Patton powder is mainly orthorhombic, and the lead powder particles are spherical, with a larger particle size than Shimadzu powder. It is easier to form 4BS through high-temperature curing, and the lead paste and the grid form a good bond. After chemical formation, it is converted into α-PbO2, forming a relatively coarse and solid skeleton and mesh structure, thereby extending the life of the battery.
[0061] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0062] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A long-life OPzV battery, consisting of a plate, a separator, a gel electrolyte, a shell, and conductive lead parts; It is characterized in that The electrode plate is composed of a positive electrode plate and a negative electrode plate. The positive electrode plate is produced by Barton, red lead is added, and it is made by extrusion and high-temperature curing process. The negative electrode plate is made by coating negative lead paste on the negative electrode grid and then curing it.
2. A long-life OPzV battery according to claim 1, characterized in that: Preparation method of Patton: Heat the lead ingot in a lead melting pot to a molten state, then introduce the 450°C lead liquid into the gas phase oxidation chamber, and introduce fresh air at the same time. In the gas phase oxidation chamber, the molten lead liquid is stirred into fine droplets by a high-speed rotating impeller, so that the lead liquid is fully in contact with the air and oxidized to form lead oxide particles. The negative pressure wind blows the conforming lead powder particles to the cyclone settler for cooling and sedimentation, and collects them through pulse bags.
3. A long-life OPzV battery according to claim 2, characterized in that: Lead powder oxidation degree 78-82%, apparent specific gravity 1.70-1.80g / cm 3 , average diameter 4μm, specific surface area 1.2~1.4m 2 / g, the particles are spherical.
4. A long-life OPzV battery according to claim 1, characterized in that: The weight ratio of barton and red lead is 3:
1.
5. A long-life OPzV battery according to claim 1, characterized in that: The lead paste raw materials in the positive plate paste extrusion process are prepared according to the following weight: 4-4.5 parts of sulfuric acid, 18-19 parts of water, 18.5-19.5 parts of red lead, and 57-59 parts of Patton powder.
6. A long-life OPzV battery according to claim 1, characterized in that: The curing temperature of the positive electrode curing process is 65-80°C, the humidity is 98%, the high temperature time is not less than 12h, and the curing process temperature is not less than 65°C.
7. A long-life OPzV battery according to claim 1, characterized in that: The negative electrode lead paste is prepared from the following raw materials by weight: 0.1-0.2 parts of lignin, 0.2-0.3 parts of acetylene black, 0.4-0.6 parts of barium sulfate, 3-4 parts of sulfuric acid, 12-14 parts of water, and 81-84.4 parts of lead powder.
8. A long-life OPzV battery according to claim 1, characterized in that: The positive plate ribs in the positive plate and the negative plate are lead-calcium-tin-aluminum alloy, and the negative plate grids are lead-calcium-tin-aluminum alloy.
9. Use of the long-life OPzV battery according to any one of claims 1 to 8 in a lead-acid battery.